2018
DOI: 10.3892/or.2018.6179
|View full text |Cite
|
Sign up to set email alerts
|

Rhus verniciflua Stokes extract induces inhibition of cell growth and apoptosis in human chronic myelogenous leukemia K562 cells

Abstract: Rhus verniciflua Stokes has been widely used as a traditional medicinal plant with a variety of pharmacological activities. We investigated the mechanisms involved in mediating the effects of Rhus verniciflua Strokes (R. verniciflua) extract in human chronic myelogenous leukemia K562 cells, including caspase-dependent apoptotic pathways related to cell-cycle arrest, as well as the inhibition of nuclear factor NF-κB activation and upregulation of the mitogen-activated protein kinase (MAPK) signaling pathway. R.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…In a high-fat diet-induced obesity mouse model, resveratrol significantly reduced CTLA-4 expression in regulatory T cells [ 161 ], demonstrating results similar to those reported elsewhere in an inflammatory bowel disease model [ 162 , 163 ]. Furthermore, studies show that active compounds in Rhus verniciflua Stokes extract, used in Korean herbal medicine, successfully blocked the expression of both PD-1/PDL-1 and CTLA-4 [ 164 , 165 , 166 ].…”
Section: Phytochemicalsmentioning
confidence: 99%
“…In a high-fat diet-induced obesity mouse model, resveratrol significantly reduced CTLA-4 expression in regulatory T cells [ 161 ], demonstrating results similar to those reported elsewhere in an inflammatory bowel disease model [ 162 , 163 ]. Furthermore, studies show that active compounds in Rhus verniciflua Stokes extract, used in Korean herbal medicine, successfully blocked the expression of both PD-1/PDL-1 and CTLA-4 [ 164 , 165 , 166 ].…”
Section: Phytochemicalsmentioning
confidence: 99%
“…Rhus verniciflua stokes (RV) is reported to have anticancer [9][10][11][12][13], anti-adipogenic [14,15], antioxidant [16], and anti-inflammatory effects [17][18][19][20][21]. Despite these beneficial effects, RV utilization is limited due to the presence of allergen urushiol in it.…”
Section: Introductionmentioning
confidence: 99%
“…Toxicodendron vernicifluum Stokes (TVS) was found to contain a number of bioactive phytochemicals, including alkaloids, polyphenols and flavonoids [12]. Previous research has shown that TVS extract has antioxidant, anti-bacterial, anti-obesity, anti-proliferative, anti-inflammatory, and anti-tumor effects [12][13][14][15][16][17][18][19][20][21][22]. Despite the beneficial pharmacological effects of TVS, its use has been somewhat limited due to the presence of urushiol an allergenic substance, that is a mixture of several derivatives of catechol.…”
Section: Introductionmentioning
confidence: 99%